Multi-material functionally graded additive manufacturing of zirconia ceramic: A systematic review - Sinan A. Shwailiya; Mahammed Rashid Hameed (Open Ceramics)
The objective of this review was to investigate dental literature for attempts including graded, layered or multi-material Additive Manufacturing of dental ceramics, with a goal to improve zirconia dental restorations, limitations related to decreased translucency and weak adhesion to tooth structure of zirconia materials may be noticed in routine dental practice. Additive Manufacturing (AM) is gaining interest as a manufacturing method that may replace Subtractive Manufacturing (SM). Functionally Graded Additive Manufacturing (FGAM) can produce a functionally graded material in 3D printing techniques; it allows for adjusting the material chemical structure and phase across its section, innovation of new composite materials and modifications of the design using a single construction step. The need for veneering and lamination of zirconia restorations inspired the authors to investigate FGAM technologies for a solution. An extensive search was conducted on experiments regarding AM to construct multi-material or graded designs, main findings were listed in a try to achieve a favorable material manufacturing technique for application in restorative dentistry.